2019
DOI: 10.1029/2019jc015330
|View full text |Cite
|
Sign up to set email alerts
|

Recent Contributions of Theory to Our Understanding of the Atlantic Meridional Overturning Circulation

Abstract: Revolutionary observational arrays, together with a new generation of ocean and climate models, have provided new and intriguing insights into the Atlantic Meridional Overturning Circulation (AMOC) over the last two decades. Theoretical models have also changed our view of the AMOC, providing a dynamical framework for understanding the new observations and the results of complex models. In this paper we review recent advances in conceptual understanding of the processes maintaining the AMOC. We discuss recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 190 publications
6
83
0
Order By: Relevance
“…5). These waves appear in the Hovmöller diagram to be slower than predicted due to the decaying amplitude of Kelvin waves, which radiate energy into the interior via westward propagating Rossby waves (Johnson and Marshall 2002). The southward Kelvin wave arrives at the southern tip of Africa (''D'' in Fig.…”
Section: A Transient Response To a Step Change In Nadw Formationmentioning
confidence: 94%
See 1 more Smart Citation
“…5). These waves appear in the Hovmöller diagram to be slower than predicted due to the decaying amplitude of Kelvin waves, which radiate energy into the interior via westward propagating Rossby waves (Johnson and Marshall 2002). The southward Kelvin wave arrives at the southern tip of Africa (''D'' in Fig.…”
Section: A Transient Response To a Step Change In Nadw Formationmentioning
confidence: 94%
“…The reduced gravity model represents the upper northward branch of the AMOC (Fig. 1) and is similar to models used in previous studies (e.g., Johnson and Marshall 2004;Allison et al 2011;Jones and Cessi 2016). However, this 1.5-layer reduced gravity model omits a number of key components of the global ocean overturning circulation, including a realistic surface forcing in the North Atlantic, which modifies the NADW formation rate, and a realistic surface schematic of the global ocean overturning circulation, adapted from Talley (2013).…”
Section: Model Description and Methodsmentioning
confidence: 99%
“…However, whether the current generation of low‐resolution climate models adequately simulates the sensitivity of the AMOC to a warming climate is still a matter of debate (e.g., Caesar et al, ; Rahmstorf et al, ) with some authors suggesting that the sensitivity in nature could be higher than previously thought (Heuzé, ; Reintges et al, ). For more exhaustive overviews about the AMOC and mechanisms driving its strength and variability we refer the reader to comprehensive reviews such as Lumpkin and Speer (2007), Kuhlbrodt et al (), Buckley and Marshall (), Zhang et al (), Johnson et al (2019) and Weijer et al ().…”
Section: Introductionmentioning
confidence: 99%
“…Most of the models considered in this study have relatively coarse resolution, including non-eddying oceans (≥ 1°x1°), which means that they might be missing some key dynamics for the AMOC (Johnson et al, 2019) that could be important to represent realistic linkages. The current analysis, however, includes two models at eddy-permitting resolution (HadGEM3-…”
mentioning
confidence: 99%
“…differences (Hirschi et al, 2020;Johnson et al, 2019). A recent analysis based on HadGEM3-GC3.1 (a later version of HadGEM3-GC2) configured at different horizontal resolutions has shown that long-standing model biases, including in the…”
mentioning
confidence: 99%